A crowdsource model for quality assurance in cloud computing. (2016) - Hussain, Mohammed; Al-Mourad, Mohamed Basel
Cloud computing has transformed the way businesses manage their IT resources. By uploading IT solution to the cloud, businesses are assured that computational power and storage capacity are available on demand. This makes cloud computing the next phase in the internet's evolution. Businesses that use Cloud Service Providers (CSPs) tend to have Service-Level Agreements (SLAs), which act as a contract and define the level of expected service from the CSP, including availability, performance and security. Third Party Auditors (TPAs) have been suggested by recent research as a means to monitor CSPs. While the use of TPAs may seem sufficient, this paper shows a method where a CSP may deceive the SLA to reduce their cost and become more competitive. The CSP may achieve that while avoiding detection by TPAs. This paper describes two methods that enable CSPs to deceive cloud users. The simulation described in this paper shows that CSPs may save considerable amounts of money. The paper also presents a crowdsourced TPA model that lays the foundation for a solution to the problem. Our model can help TPAs to monitor CSPs and consequently detect any divergence from stated SLAs.